Persepsi Remaja Terhadap Upaya Bunuh Diri dalam Film “Kembang Api” - Farhan Aditya Danendra; Augustin Mustika Chairil (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
This mass Media can be the main media in mass communication activities that aim to spread messages to audiences. Film is a persuasive type of mass media. movies can greatly affect people's perception of the storyline and the message contained in the film. One of the problems in society is suicide. Suicide is a serious issue that can have a negative impact on a person's mental health. Films have a significant role in shaping adolescents ' perceptions of various issues, including suicide attempts. However, there is still a lack of understanding about teenagers ' perception of suicide scenes in films. Therefore, this study will fill this knowledge gap by analyzing adolescents ' perceptions of suicide scenes in the movie "Fireworks”. This study aims to describe adolescents ' perception of suicide attempts in fireworks films. This study uses qualitative research methods by using perceptual analysis. This method views the message Maker creates a message in such a way with a certain meaning that is expected to be accepted by the audience. The results showed that there are differences in perception between informants with each other. Audiences conduct negotiations based on their knowledge and experience. Based on the results of the study, the researcher concluded that the aspects presented in this study do not completely agree. the meaning of each informant moves by itself from one position to another. Such interpretations come from knowledge, experience gained from their environment.